Abrasion Resistance of Plastic Parts Manufactured By 3D Printing - Hriţuc, Adelina; Slătineanu, Laurenţiu; Sover, Alexandru; Mihalache, Andrei Marius; Surugiu, Ioan; Coteaţă, Margareta (Bulletin of the Polytechnic Institute of Iași. Machine Constructions Section, 2022)
There are situations where parts manufactured by 3D printing processes must have a high abrasion resistance. To conduct experimental research on this subject, relatively simple test equipment for abrasive wear of pin-on-disk type was designed and materialized. The test pieces from the research material were pressed with known forces on the surface of a rotating abrasive paper disk. The test pieces were made of polyethylene terephthalate PET and polyethylene terephthalate carbon fiber reinforced PET CF15. As output parameters, the speed of decreasing the mass and the length of the test piece were used, respectively, for predetermined test durations. An experimental Taguchi L8 program was used, with 7 independent variables at two levels of variation. The experimental results were mathematically processed determined empirical mathematical models of the power function type. It was found that the strongest influence on the values of the output parameters was exerted by the average travel speed and by the granulation of the particles incorporated in the abrasive paper disk.